Religious and educational activities of theologian Nurgali Khasanov - R.I. Malikov (Ученые записки Казанского университета: Серия Гуманитарные науки)
In this paper, the biography of Nurgali Khasanov was compiled for the first time. The personality of Nurgali Khasanov, a famous religious figure of the Middle Volga region during the pre-revolutionary period, has been poorly studied despite he was a recognized theologian and an associate of Shihab al-Din al-Marjani, a Tatar scholar. Nurgali Khasanov was also the head of the Madrasah of Buinsk over more than 30 years – he educated and brought up many students, of whom more than 100 became the acting mullahs and 14 were the famous Tatar public and religious figures of the late 19th – early 20th centuries. His merits were recognized by the authorities of the Russian and Ottoman Empires, from whom he received government awards. In this paper, we introduced more than 10 works and publications written by Nurgali Khasanov – they were found in Russian libraries, some proved helpful for description of his life path – into science. Thus, the paper is based on a wide range of sources and literature and presents in detail the multifaceted life and religious and educational activities of Nurgali Khasanov.